A Cryogenic Process for Antisolvent‐Free High‐Performance Perovskite Solar Cells. Issue 44 (12th September 2018) - Ng, Annie; Ren, Zhiwei; Hu, Hanlin; Fong, Patrick W. K.; Shen, Qian; Cheung, Sin Hang; Qin, Pingli; Lee, Jin‐Wook; Djurišić, Aleksandra B.; So, Shu Kong; Li, Gang; Yang, Yang; et al.
Abstract: A cryogenic process is introduced to control the crystallization of perovskite layers, eliminating the need for the use of environmentally harmful antisolvents. This process enables decoupling of the nucleation and the crystallization phases by inhibiting chemical reactions in as‐cast precursor films rapidly cooled down by immersion in liquid nitrogen. The cooling is followed by blow‐drying with nitrogen gas, which induces uniform precipitation of precursors due to the supersaturation of precursors in the residual solvents at very low temperature, while at the same time enhancing the evaporation of the residual solvents and preventing the ordered precursors/perovskite from redissolving into the residual solvents. Using the proposed techniques, the crystallization process can be initiated after the formation of a uniform precursor seed layer. The process is generally applicable to improve the performance of solar cells using perovskite films with different compositions, as demonstrated on three different types of mixed halide perovskites. A champion power conversion efficiency (PCE) of 21.4% with open‐circuit voltage ( V OC ) = 1.14 V, short‐circuit current density ( J SC ) = 23.5 mA cm −2, and fill factor (FF) = 0.80 is achieved using the proposed cryogenic process. Abstract : A novel cryogenic process has universal applicability to prepare mixed perovskite films. Excellent film quality and consequently promising device performance result from decoupling of nucleation and crystallization phases during the formation of perovskites. The cryogenic temperature suppresses premature reactions of the precursors and prevents premature coalescence of nuclei into large crystallites, enabling uniform film formation following the blow‐drying and annealing processes.